The good tourist, the bad refugee and the ugly German: Xenophobic activities and tourism - Marek Endrich; Stephan Michel (University of Hamburg, Institute of Law and Economics (ILE), 2018)
Germany shows a more welcoming attitude towards refugees than most other European countries. At the same time, the influx of refugees has led to massive protests, demonstrations and attacks against refugees. We look at the economic effects of these demonstrations and attacks on one important industry, namely tourism. Combining a novel, district-level data set on tourism with data on xenophobic activities, we find that xenophobic demonstrations have negative effects on tourist arrivals. This effect is found for domestic and foreign tourists.
Keywords: F22; L83; 330; Xenophobic activities; refugees; tourism; district-level data